Copper-based nano-enzyme and membrane filter loaded with copper-based nano-enzyme
By designing and loading high-active copper-based nanoenzymes onto nylon membranes, the problems of natural laccases decreased activity and unsolid nanoenzyme load in extreme environments are solved, and efficient pollutant degradation and stability in extreme environments are achieved avoids secondary pollution.
Patent Information
- Application Number
- CN202411305790.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-07
AI Technical Summary
Natural laccase activity decreases in extreme environments, and the nanoenzyme-loaded membrane filter has problems such as insolid binding, easy shedding and reduced activity, resulting in difficulty in recycling and secondary contamination.
Design a high activity and high stability copper-based nanoenzyme (GA-Cu) which is prepared by reaction of glutathione, 2-aminoimidazole and CuCl2·2H2O in N,N-dimethylformamide, and It is loaded onto a nylon membrane, and uses chitosan as a binder to form a dense and stable composite membrane through vacuum suction filtration.
High tolerance and excellent reusability in extreme environments are achieved, the shedding and activity of nanoenzymes are avoided, and the efficiency of pollutant degradation is improved.
Smart Images

Figure CN119264157A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental protection, and specifically relates to a copper-based nanozyme and a membrane filter loaded with the copper-based nanozyme. Background Art
[0002] Laccase is a multi-copper oxidase found in Japanese lacquer tree. Since the reduction product of laccase oxidation is water, it becomes a green and environmentally friendly catalyst; at the same time, it has a wide range of substrates, can catalyze a variety of phenolic compounds, and can effectively degrade pollutants in water. Therefore, laccase can be used to treat environmental pollutants in industrial wastewater, and has been successfully applied to papermaking, food, pharmaceutical and other industries. However, the defects of laccase itself also limit its large-scale application. Natural laccase often has inherent defects such as high price, poor stability, and difficult recycling. For example, the activity of natural laccase drops sharply in alkaline environment, environment above 60°C, and environment with high ion concentration.
[0003] Compared with natural enzymes, nanozymes have the advantages of simple preparation, low cost, high stability and easy large-scale production. However, most nanozymes are in powder form, so free nanozymes are difficult to recycle during use and are prone to secondary pollution. Although loading nanozymes on membranes to prepare membrane filters can effectively overcome the problems of free nanozymes being difficult to recycle and prone to secondary pollution during use, nanozymes may not be firmly bound and easily fall off after being loaded on the membrane, and the activity of the nanozymes may even decrease sharply.
[0004] Inspired by the active center of natural laccase, this application designed a copper-based nanozyme with high activity and high stability, and loaded it on a nylon membrane to make a membrane filter. Summary of the invention
[0005] One of the purposes of the present invention is to provide a copper-based nanozyme, which is prepared by the following method: glutathione, 2-aminoimidazole and CuCl2·2H2O are added to N,N-dimethylformamide and mixed, stirred for reaction at 180°C for 3-6 hours, and the reactant is centrifuged and the precipitate is collected to obtain the copper-based nanozyme; The molar ratio of glutathione, 2-aminoimidazole and CuCl2·2H2O is 0.5-1.5:0.1-2.0:0.1-1.
[0006] The second object of the present invention is to provide the application of the above copper-based nanozyme in catalytic degradation of environmental pollutants.
[0007] The third object of the present invention is to provide a membrane filter, wherein the membrane filter uses a nylon membrane as a base membrane, and the copper-based nanozyme is loaded on the surface of the base membrane.
[0008] Furthermore, the membrane filter is prepared by the following steps: Step 1, vacuum-filtering the copper-based nanozyme suspension onto a nylon-based membrane, and drying at 60°C-80°C to obtain a GA-Cu / nylon membrane, wherein the concentration of the copper-based nanozyme suspension is 3-8 mg / 20 mL of water; Step 2, adding the copper-based nanozyme to the acetic acid solution of chitosan, stirring, and obtaining a GA-Cu@CS solution, wherein the amount ratio of the copper-based nanozyme to chitosan is 12.8-30 mg: 30 mg, and the concentration of chitosan in the acetic acid solution of chitosan is 0.5 wt.%; Step 3, vacuum-filtering the GA-Cu@CS solution onto the prepared GA-Cu / nylon membrane, and drying at 60° C. after filtration to obtain a composite filtration membrane.
[0009] A fourth object of the present invention is to provide the use of the above membrane filter in catalytic degradation of environmental pollutants.
[0010] The prior art (Preparation of laccase mimicking nanozymes and their catalytic oxidation of phenolic pollutants) synthesized a laccase mimic CA-Cu by coordinating copper with cysteine-aspartic acid dipeptide. The GSH and 2-aminoimidazole used in the present invention can form a peptide bond as an electron transfer bridge for electron transfer in redox reactions; the -SH in GSH can transfer Cu 2+ Reduction to Cu + , another molecule Cu 2+ Combined with the imidazole group, the coexistence of multiple valence states can promote electron transfer; the long chain of GSH also helps to form a large cavity structure, which can accommodate more substrates for reaction.
[0011] The present invention uses Cu 2+ As the active center, 2-aminoimidazole and glutathione as ligands, a GA-Cu nanozyme with high activity and high stability was designed and synthesized. Subsequently, chitosan was used as an adhesive and the nanozyme was loaded onto the nylon membrane by vacuum-assisted filtration. Since GA-Cu nanozyme has abundant N, O electron donors and -OH groups, it can interact with the abundant -OH and -NH groups on chitosan in the functional layer through H bonds to form a dense and stable composite membrane.
[0012] The present invention uses a one-pot method to synthesize GA-Cu, and optimizes the synthesis conditions, such as temperature, time, and substrate ratio, to achieve optimal enzyme activity; the synthesized nanozyme has strong tolerance to extreme environments, and also has excellent reusability and storage stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The scanning electron microscope spectra (A) and transmission electron microscope spectra (B) of GA-Cu.
[0014] Figure 2 This is the powder crystal diffraction spectrum of GA-Cu.
[0015] Figure 3 This is the X-ray photoelectron spectrum of GA-Cu.
[0016] Figure 4 The results of UV-visible absorption spectroscopy were used to study the laccase-like activity of GA-Cu.
[0017] Figure 5 Relative activities of GA-Cu and laccase at the same mass concentration under different pH (A), temperature (B), salt concentration (C), ethanol concentration (D), storage time (E) and cycle period (F).
[0018] Figure 6 Michaelis-Menten curve (A) and Lineweaver-Burk double reciprocal plot (B) of GA-Cu for 2,4-DP.
[0019] Figure 7 Scanning electron microscope images of the top surface (A) and cross section (B) of the GA-Cu@CS / GA-Cu / nylon film.
[0020] Figure 8 This is the degradation effect of GA-Cu@CS / GA-Cu / nylon membrane on 2,4-DP.
[0021] Fig. 9 The degradation effect (A) and the filtrate volume per hour (B) of the composite membranes with different dry weight ratios, as well as the degradation effect (C) and the filtrate volume per hour (D) of the composite membranes with or without a pre-functional layer.
[0022] Fig.10 The HPLC spectra of the original solution and the filtrate are compared (A); and the HPLC spectra of the original solution and the desorbed solution are compared (B). DETAILED DESCRIPTION
[0023] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.
[0024] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0025] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0026] Laccase was purchased from Shanghai Yuanye Biotechnology Co., Ltd. Example 1
[0027] 1. Preparation of copper-based nanozymes (GA-Cu) 1 mL 0.24 M glutathione (GSH), 1 mL 0.24 M 2-aminoimidazole, 0.5 mL 0.48 M CuCl2·2H2O and 2 mL DMF were mixed and stirred at 180 ° C for 5 h. The reaction mixture was centrifuged at 12000 rpm for 3 min, and the precipitate was collected and washed with DMF and water three times respectively. Finally, the precipitate was freeze-dried for 8 h to obtain the nanozyme GA-Cu.
[0028] like Figure 1 As shown in Figure A, GA-Cu is a uniform sphere with a rough and porous surface and a diameter of about 600 nm. Figure 1 As shown in Figure B, GA-Cu has a good crystal structure and clear lattice fringes. Figure 2 As shown in the figure, the powder crystal diffraction spectrum of GA-Cu shows that GA-Cu has a crystalline form; after analysis by Digital Micrograph software, the lattice spacing of GA-Cu is 0.287 nm. Figure 3 As shown, the full scan spectrum indicates the presence of S, C, N, O, and Cu elements in GA-Cu, which is consistent with the ligands and copper ions used.
[0029] Four groups of experiments were set up: (a) 2,4-dichlorophenol (2,4-DP) + 4-aminoantipyrine (4-AP), (b) 2,4-dichlorophenol (2,4-DP) + nanozyme, (c) 4-aminoantipyrine (4-AP) + nanozyme, (d) 2,4-dichlorophenol (2,4-DP) + 4-aminoantipyrine (4-AP) + nanozyme; GA-Cu aqueous solution (1 mg / mL, 100 μL), 2,4-dichlorophenol (1 mg / mL, 100 μL), 4-aminoantipyrine (1 mg / mL, 100 μL) and 2-morpholineethanesulfonic acid buffer (30 mM, pH 6.8) were mixed according to the set groups, and the final concentrations of 2,4-dichlorophenol, 4-aminoantipyrine and GA-Cu after mixing were all 0.1 mg / mL. The four groups of samples were reacted at room temperature for 30 min, and the absorbance of the solution was measured after the reaction. Figure 4 As shown, only the fourth group had obvious UV absorption at 510 nm, proving that GA-Cu had laccase-like activity.
[0030] 2. Investigation of GA-Cu catalytic performance (1) Take GA-Cu or laccase solution (1 mg / mL, 100 μL) and mix 2,4-DP (1 mg / mL, 100 μL), 4-AP (1 mg / mL, 100 μL), and 2-morpholineethanesulfonic acid buffer (30 mM, pH6.8 700 μL) evenly, react at 25°C for 30 min, centrifuge at 12000 rpm for 3 min, and detect the absorbance at 510 nm to evaluate its catalytic activity. In the same way, GA-Cu and laccase were dispersed in MES buffer solutions of pH 4, pH5, pH6, pH7, pH8, pH9, and pH10 and incubated for 1 h. The relative activity can be obtained by comparing with the activity at pH 6.8 or pH 7. Figure 5 As shown in Figure A, the stability of GA-Cu is higher than that of laccase under both acidic and alkaline conditions, especially under alkaline conditions. When the pH exceeds 7, the activity of laccase drops sharply, while GA-Cu can still maintain more than 80% of its activity.
[0031] (2) GA-Cu or laccase aqueous solution (1 mg / mL, 100 μL) was mixed with 2,4-DP (1 mg / mL, 100 μL), 4-AP (1 mg / mL, 100 μL), and MES buffer (30 mM, pH 6.8, 700 μL), and reacted for 30 min at different temperatures (20°C, 30°C, 40°C, 50°C, 60°C, 70°C, and 80°C), centrifuged at 12,000 rpm for 3 min, and the absorbance was measured at 510 nm to evaluate its catalytic activity. The effect of temperature on GA-Cu and laccase was explored, and the relative activity can be obtained by comparing it with the activity at 30°C. Figure 5 As shown in B, the optimal reaction temperature for both is 30°C, after which their activities decrease as the temperature rises; laccase is completely inactivated at 70°C, while GA-Cu maintains about 70% of its activity.
[0032] (3) GA-Cu and laccase were dispersed in aqueous NaCl solutions of different concentrations (0, 50, 100, 300, and 500 mM) and incubated for 1 h. The GA-Cu or laccase aqueous solution (1 mg / mL, 100 μL) was mixed evenly with 2,4-DP (1 mg / mL, 100 μL), 4-AP (1 mg / mL, 100 μL), and MES buffer (30 mM, pH 6.8, 700 μL). The mixture was reacted at 25°C for 30 min, centrifuged at 12,000 rpm for 3 min, and the absorbance was measured at 510 nm to evaluate its catalytic activity. The relative activity can be obtained by comparing it with the activity at 0 mM NaCl. Figure 5As can be seen in Figure C, the catalytic activity of laccase decreases sharply with the increase of NaCl concentration. This is because under high ionic strength, the charge distribution and spatial structure of the enzyme will be greatly affected, resulting in a serious loss of activity; however, GA-Cu still maintains more than 75% activity at a NaCl concentration of 500 mM.
[0033] (4) GA-Cu and laccase were incubated in ethanol solutions of different concentrations (0, 25%, 50%, 70% and 100% v / v) for 1 h, and GA-Cu or laccase solution (1 mg / mL, 100 μL) was mixed with 2,4-DP (1 mg / mL, 100 μL), 4-AP (1 mg / mL, 100 μL), and MES buffer (30 mM, pH 6.8, 700 μL). The mixture was reacted at 25°C for 30 min, centrifuged at 12,000 rpm for 3 min, and the absorbance was measured at 510 nm to evaluate its catalytic activity. The relative activity can be obtained by comparing it with the activity in 0% ethanol solution. Figure 5 As shown in D, with the increase of ethanol concentration, the catalytic activities of both decreased; when the ethanol concentration reached 70%, laccase was completely inactivated while GA-Cu maintained more than 80% of its activity.
[0034] (5) GA-Cu and laccase were dispersed in deionized water, respectively, and stored at 2-8°C. The catalytic activity of GA-Cu and laccase was measured every 2 days. The GA-Cu or laccase aqueous solution (1 mg / mL, 100 μL) was mixed with 2,4-DP (1 mg / mL, 100 μL), 4-AP (1 mg / mL, 100 μL), and MES buffer (30 mM, pH 6.8, 700 μL). The mixture was reacted at 25°C for 30 min, centrifuged at 12,000 rpm for 3 min, and the absorbance was measured at 510 nm to evaluate its catalytic activity. The relative activity can be obtained by comparing it with the activity at day 0. Figure 5 As shown in E, laccase was completely inactivated after 10 days. In contrast, the catalytic activity of GA-Cu remained above 80% after 20 days.
[0035] (6) The reusability of the enzyme is a useful property for continuous operation and cost reduction. 2,4-DP (1 mg / mL, 100 μL), 4-AP (1 mg / mL, 100 μL), MES buffer (30 mM, pH 6.8, 700 μL) and GA-Cu aqueous solution (1 mg / mL, 100 μL) were reacted at 25°C for 30 min, and the absorbance at 510 nm was measured. After each reaction, the mixed solution was centrifuged at 12,000 rpm for 3 min and washed once with DMF. The obtained GA-Cu was used for the next color development reaction. Figure 5 As shown in Figure 5(F), the catalytic activity of GA-Cu remains above 80% after 8 cycles.
[0036] In summary, GA-Cu exhibited remarkable catalytic stability and reusability compared with natural laccase.
[0037] 3. In order to study the catalytic kinetic properties of GA-Cu, the reaction rate of different concentrations of 2,4-DP was determined. Different concentrations of 2,4-DP (10, 20, 40, 60, 80, 100, 120, 150, 180, 210, 250, 300, 350, 400, 450 μg / mL) were mixed with 0.08 mg / mL GA-Cu aqueous solution and 0.15 mg / mL 4-AP for 5 min. The absorbance at 510 nm was recorded within 5 min to determine the initial reaction rate. The kinetic parameters were calculated according to the Michaelis-Menten equation. and .like Figure 6 As shown, GA-Cu The value was 0.1791 mM, which was much lower than that of laccase, indicating that it had a much higher affinity for the substrate than laccase. The value is 7.53 mM / min, which is slightly higher than that of laccase, indicating that it can degrade the substrate faster. These kinetic parameters show that GA-Cu has better catalytic activity than natural laccase. In addition, compared with other reported laccase-like nanozymes, GA-Cu exhibits higher catalytic activity. Example 2
[0038] 1. Preparation of GA-Cu@CS / GA-Cu / nylon composite membrane First, the pre-functional layer was filtered, and 5 mg of GA-Cu nanozyme was added into 20 mL of water and ultrasonically dispersed for 30 min. The nanozyme suspension was vacuum filtered onto a nylon-based membrane (Haining YiBo, model: membrane diameter 50 mm, pore size 0.05 μm), and dried at 60 °C for 5 min to obtain a GA-Cu / nylon membrane.
[0039] Subsequently, 12.8 mg, 20 mg, and 30 mg of nanozyme powder were added to 6 mL of 1% acetic acid solution containing 30 mg of chitosan, respectively, and the mixture was stirred for 4 h to obtain GA-Cu@CS solutions containing 30, 40, and 50 wt% (dry weight) of nanozyme, respectively, where dry weight = mass of GA-Cu / total mass of GA-Cu and chitosan.
[0040] Finally, the functional layer was filtered, and the GA-Cu@CS solution was vacuum filtered twice (3 mL each time) onto the prepared GA-Cu / nylon membrane. After each filtration, the composite membrane was dried at 60°C for 5 min to obtain a GA-Cu@CS / GA-Cu / nylon composite membrane.
[0041] like Figure 7 As shown in Figure A, the SEM spectrum of the top surface of the composite membrane shows that GA-Cu is evenly dispersed on the base membrane, and the chitosan attached to GA-Cu acts as a binder; Figure 7 As shown in Figure 2B, the SEM image of the cross section again confirms that a thin GA-Cu@CS layer is formed on the substrate and is firmly attached to the membrane.
[0042] Use the composite membrane to filter the 0.5 mg / mL 2,4-DP solution, and add 4-AP to the filtrate for color development. Figure 8 As shown, the prepared composite membrane can be used for the removal of environmental pollutants.
[0043] 2. Evaluation of GA-Cu@CS / GA-Cu / nylon membrane performance (1) Effect of GA-Cu loading on the performance of GA-Cu@CS / GA-Cu / nylon membrane The degradation effect of the membrane and the amount of filtrate per hour are two important indicators for evaluating membrane performance. It is necessary to comprehensively consider the above two indicators to select the most appropriate loading capacity.
[0044] The degradation effect of the membrane was evaluated by filtering and degrading 2,4-DP and measuring the absorbance of the filtrate. The prepared composite membrane was cut into small discs of suitable size, and 6 small discs were placed in a filtration device as a group. Then, a mixed solution of 2,4-DP (5 mg / mL, 5 mL) and MES (30 mM, pH 6.8, 45 mL) was added to the device, and filtered at a pressure of 0.2 MPa, and the filtrate was collected every hour. 2 mL of the filtrate was mixed with 0.5 mL of 4-AP (2 mg / mL), and the absorbance at 510 nm was measured after reacting at 25 °C for 30 min. The catalytic performance of the composite membrane was evaluated by the absorbance. At the same time, the filtration performance of the composite membrane was evaluated by the volume of the filtrate obtained after filtration for 1 h.
[0045] Fig. 9 Figure A shows the absorbance of composite membranes with different GA-Cu loadings. The degradation effect of the membrane with 50% dry weight within 4 h is equivalent to that of the membrane with 40% dry weight; while the degradation effect of the membrane with 30% dry weight is significantly lower than the other two. Fig. 9 As shown in B, in terms of the amount of filtrate per hour, the membrane with a dry weight of 40% is significantly higher than the other two membranes, which is 8.83-11 mL; the membrane with a dry weight of 30% has a filtrate volume of 6.75-9.5 mL per hour. The possible reason is that the amount of nanozymes is relatively small and the amount of chitosan is relatively large, which makes the nanozymes in the system act as adhesives, and chitosan is a non-porous structure, so there are relatively few pores on the membrane surface and the amount of filtrate is also small; the membrane with a dry weight of 50% has a filtrate volume of 6.5-8.83 mL per hour. The possible reason is that the amount of nanozymes is too much, resulting in a too thick membrane layer, too many paths in the membrane, and the filtrate needs to travel a longer distance through the membrane layer, which ultimately leads to a reduction in the amount of filtrate; and for the membrane with a dry weight of 40%, the ratio of nanozymes to chitosan is just balanced, and the amount of filtrate is the largest.
[0046] In addition, among the three membranes, the nanozymes on the membranes with a dry weight of 30% and 40% were more tightly bound to the membranes, while the nanozymes on the membranes with a dry weight of 50% were easier to fall off, and there was obvious nanozyme falling off at the edge of the membrane when cutting. In summary, the degradation effects of the membranes with a dry weight of 40% and 50% were similar, but the 40% membrane had more filtrate per hour, so 40% was the optimal ratio.
[0047] (2) Effect of the presence or absence of a pre-functional layer on the degradation effect of the composite membrane A composite membrane without a pre-functional layer with a dry weight of 40 wt% was prepared. Specifically, first, 20 mg of nanozyme powder was added to 6 mL of an aqueous solution (containing 1% acetic acid) containing 30 mg of chitosan (CS), and the mixture was stirred for 4 h to obtain a GA-Cu@CS solution containing 40 wt% (dry weight) of nanozymes; then the functional layer was filtered, and the GA-Cu@CS solution was vacuum filtered onto a nylon-based membrane twice (3 mL each time), and after each filtration, the composite membrane was dried at 60°C for 5 min to obtain a composite membrane without a pre-functional layer.
[0048] The degradation effect of the membrane was evaluated by filtering and degrading 2,4-DP using composite membranes with or without pre-functional layers, and the absorbance of the filtrate was measured. The prepared composite membrane was cut into small discs of suitable size, and 6 small discs were placed in a filtration device as a group. Then, a mixed solution of 2,4-DP (5 mg / mL, 5 mL) and MES (30 mM, pH 6.8, 45 mL) was added to the device, and filtered at a pressure of 0.2 MPa, and the filtrate was collected every hour. 2 mL of the filtrate was mixed with 0.5 mL of 4-AP (2 mg / mL), and the absorbance at 510 nm was measured after reacting at 25°C for 30 min. The catalytic performance of the composite membrane was evaluated by the absorbance. At the same time, the filtration performance of the composite membrane was evaluated by the volume of the filtrate obtained after 1 h of filtration. Fig. 9 Figures C and D show the degradation effect and hourly filtrate volume of the two membranes. It can be seen that the presence or absence of a pre-functional layer has little effect on the degradation effect of the composite membrane, but the composite membrane containing a pre-functional layer has significantly more filtrate volume per hour. One possible reason is that when there is no pre-functional layer, chitosan directly contacts the nylon membrane, and chitosan has a high viscosity and a non-porous structure. After contacting the basement membrane, it blocks the membrane pores and causes a decrease in filtrate volume. The presence of a pre-functional layer can play a buffering role. On the one hand, it can prevent CS from directly contacting the basement membrane, and on the other hand, it also plays a role in connecting the basement membrane and the functional layer. Therefore, the presence of a pre-functional layer is very necessary. Example 3
[0049] Membrane filter filtration and degradation of tetracycline Tetracycline is an antibiotic widely used in human treatment and animal disease control. Its large accumulation in the environment poses a great risk to the ecosystem and human health. Therefore, the purification of tetracycline has attracted widespread attention.
[0050] First, a 50 mg / L TC solution was prepared and passed through a 40 wt% composite membrane at a pressure of 0.15 MPa. The filtrate was collected and analyzed by HPLC. Fig.10 As shown in A, TC was almost completely removed after one filtration. In addition, the filtrate was analyzed for total organic carbon content (TOC). The TOC of the solution before and after filtration was 15.60 mg / L and 4.20 mg / L, respectively. The large reduction in TOC after one filtration also indirectly proves that TC was removed in large quantities, and some TC was degraded more thoroughly, from organic carbon mineralization to inorganic carbon such as CO2.
[0051] Considering the potential adsorption of TC by nylon-based membranes, the residual TC on the membrane was desorbed after filtration. The composite membrane was cut into pieces, 2 mL of methanol was added and ultrasonicated for 1 h. The desorbed solution was used for HPLC analysis. The results are shown in Figure 2. Fig.10As shown in B, 9.85% of TC was obtained in the first desorption and 2.06% of TC was obtained in the second desorption, indicating that the composite membrane can degrade more than 80% of TC after one filtration.
[0052] Afterwards, the main transformation products were identified by LC-MS, and the results showed that GA-Cu had an excellent degradation effect on TC.
Claims
1. A copper-based nanozyme, characterized in that: The method is as follows: glutathione, 2-aminoimidazole and CuCl2·2H2O are added to N,N-dimethylformamide and mixed, and the mixture is stirred at 180°C for 3-6 hours, and the reactant is centrifuged and the precipitate is collected to obtain the copper-based nanozyme; The molar ratio of glutathione, 2-aminoimidazole and CuCl2·2H2O is 0.5-1.5:0.1-2.0:0.1-1.
2. Use of the copper-based nanozyme described in claim 1 in catalytic degradation of environmental pollutants.
3. A membrane filter, characterized in that The membrane filter uses a nylon membrane as a base membrane, and the copper-based nanozyme according to claim 1 is loaded on the surface of the base membrane.
4. The membrane filter according to claim 3, characterized in that Prepared using the following steps: Step 1, vacuum filtering the copper-based nanozyme suspension onto a nylon-based membrane, and drying at 60°C-80°C to obtain a GA-Cu / nylon membrane, wherein the concentration of the copper-based nanozyme suspension is 3-8 mg / 20 mL water; Step 2, adding the copper-based nanozyme to the acetic acid solution of chitosan, stirring, and obtaining a GA-Cu@CS solution, wherein the amount ratio of the copper-based nanozyme to chitosan is 12.8-30 mg: 30 mg, and the concentration of chitosan in the acetic acid solution of chitosan is 0.5 wt.%; Step 3, vacuum-filtering the GA-Cu@CS solution onto the prepared GA-Cu / nylon membrane, and drying at 60° C. after filtration to obtain a composite filtration membrane.
5. Use of the membrane filter according to claim 3 in catalytic degradation of environmental pollutants.